George Sand's volcanic imagination. (3rd April 2021) - Illingworth, James
ABSTRACT: This article proposes that George Sand can be considered as an ecofeminist. While Sand's texts have often been associated with the natural world, this association has seldom been positive, and has come to define her position in the canon, with her bucolic idealism separating her from the 'realist' approach that came to typify the nineteenth-century novel. Shifting the focus from Sand's depiction of the fields to her representations of volcanoes, this article argues that Sand's engagement with the natural environment has political connotations that are inseparable from her commitment to undoing gendered subjugation. While the volcano connects Sand to the arch-Romantic notions of transcendence and reverie and therefore to the sublime, analyses of texts including Histoire du rêveur (1831), Indiana (1832) and Laura (1864) show that not only is the volcano linked to creativity but also represents for Sand the potential for destruction and therefore renewal.